1997
DOI: 10.1002/(sici)1097-0274(199707)32:1<51::aid-ajim7>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Proportionate mortality among unionized construction operating engineers

Abstract: This report presents the results of proportionate mortality ratios (PMR) and proportionate cancer mortality ratios (PCMR) among 15,843 members of the International Union of Operating Engineers who had died between 1988–1993. Operating engineers represent one of the 15 unions in the Building and Construction Trades Department and are responsible for the operation and maintenance of heavy earthmoving equipment used in the construction of buildings, bridges, roads, and other facilities. Using U.S. proportionate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 42 publications
0
26
0
1
Order By: Relevance
“…Elevated rates of suicide among construction workers compared with the general working male population have been identified in many countries including Finland [7], the USA [8][9][10][11][12], Korea [13], Denmark [14], the UK [15,16], Canada [17], and Australia [18][19][20]. This may be because the construction workforce is largely male [21] and, in many countries, male rates of suicide are up to four times that of women [22].…”
Section: Suicide Among Construction Workersmentioning
confidence: 99%
“…Elevated rates of suicide among construction workers compared with the general working male population have been identified in many countries including Finland [7], the USA [8][9][10][11][12], Korea [13], Denmark [14], the UK [15,16], Canada [17], and Australia [18][19][20]. This may be because the construction workforce is largely male [21] and, in many countries, male rates of suicide are up to four times that of women [22].…”
Section: Suicide Among Construction Workersmentioning
confidence: 99%
“…Research in Australia and abroad has demonstrated elevated rates of suicide amongst tradesmen and construction workers compared with the general working male population [811]. To investigate industry-specific patterns in Queensland suicides, Anderson and colleagues [5] compared data from 7,652 suicides in the Queensland Suicide Register with population data from the ABS for 1990–2006.…”
Section: Introductionmentioning
confidence: 99%
“…28 In the other study, the PMR result was not confirmed in the PCMR analysis, owing to an increased mortality from many neoplasms in that study population. 13 In the remaining studies of heavy equipment operators, 11,12,18,29,30 including the only one that included a detailed assessment of DE exposure, 11,12 no increased risk of leukemia was detected. In light of these results, no conclusion can be drawn on the presence of an increased risk of leukemia in this group of workers.…”
Section: Discussionmentioning
confidence: 99%
“…12 An additional proportionate mortality study was conducted among 15,843 members of a U.S. union of construction operating engineers who died during 1988 -1993. 13 Calculation of expected deaths was based on national rates. The PMR of leukemia was 1.19 (95% CI ϭ 1.02-1.37).…”
Section: Cohort Studiesmentioning
confidence: 99%
See 1 more Smart Citation